Development of a Dashboard for Drone-Assisted High-Altitude Cellular Network Coverage - Mohd Shaid, Muhammad Akif; Che Seman, Fauziahanim (Evolution in Electrical and Electronic Engineering, 2025)
The continuous demand for enhanced cellular networks has driven crucial improvements in network assessment methods. Traditional drive and walk tests, however, face challenges such as limited altitude assessment and difficulty in accessing hard-to-reach areas. To overcome these limitations, this project concentrated on developing a drone-assisted system for real-time cellular coverage monitoring. This system features a dashboard, built with Python’s PyQt5 and PyQtGraph libraries, for visualizing LTE parameters like RSRP, RSRQ, and SINR in real-time. Heatmaps were generated using the Folium library to visualize network coverage on an interactive map. A comprehensive drive test was conducted around Parit Raja using G-NetTrack Lite and Mikrotik LtAP LTE6 Kit to collect LTE data, and a comparison between both tools was performed. A drone integrated with the Mikrotik LtAP LTE6 Kit was utilized for high-altitude LTE data collection at 10 meters and 20 meters. The dashboard was then integrated into a software user interface for ease of usability. Based on the results, it was concluded that the average percentage difference between RSRP values from G-NetTrack Lite and the Mikrotik LtAP LTE6 Kit was 7.93%. Furthermore, drone-assisted data collection revealed an overall trend suggesting a more consistent and pronounced improvement in RSRP at 20 meters altitude compared to 10 meters. Finally, the dashboard successfully fetched and visualized LTE data at one-second intervals.